A kényelmetlen nagyúr : gróf Bánffy Miklós helye és szerepe a magyar politikai életben 1940 és 1944 között - Murádin, János Kristóf (Közép-Európai Közlemények, 2015)
The study deals with the last period of political career of count Miklós Bánffy, one of the most important politicians of the Hungarian community from Transylvania in the 20th century. There are described the main political circumstances in Transylvania and Hungary between 1940 and 1944, wich influenced the final period of political activity of count Miklós Bánffy. There are presented his position in the political life of Northern Transylvania, than part of Hungary, as well, as his role information of the whole national politics in that time. The study focuses on the political battles between the two great ideologies of those times: classical liberalism and conservatorism, by presenting the two most important personalities of these basic ideas in Northern Transylvania, count Miklós Bánffy and count György Bethlen. There is described their influence on the Hungarian national politics, and on the Northern Transylvanian politics too. The main objective of the study is to complete the general imagine based on former researches about Miklós Bánffy’s personality, and his political purposes. In the study there are discussed the relations between the Hungarian majority and Romanian minority communities in Northern Transylvania in order to make more understandable the way of thinking of count Miklós Bánffy in the ethnic problem, the most important issue of the Transylvanian political life. The source material of the study consists of documents from archives, published collections of documents, specialist books, published and on-line studies, memoires and contemporary press.